MULTIDISCIPLINARY ANALYSIS OF UNCONVENTIONAL METHODS OF SPECIAL FORCES AND THEIR IMPACT ON NATIONAL AND INTERNATIONAL SECURITY (Security Dialogues, 2025)
This research examines the unconventional tactics and strategies inherent in specialforces, focusing on methods such as diversion, sabotage, assassination, and subversion. Weanalyse how these strategies affect national and international security using a multidisciplinaryapproach that incorporates theoretical frameworks from criminology, political science, andsecurity studies. The article reveals the complex interactions between special tactics andbroader security dynamics, highlighting how they can simultaneously serve as instruments toachieve political goals and raise significant ethical and legal dilemmas. The research resultsprovide deeper insight into the mechanisms of special operations and their consequences,offering practical guidelines for shaping effective responses to security challenges in themodern world. This article is not only theoretically relevant but also has direct practicalimplications for security policies and strategies at the global level.